Benzothiophene Carboxylate Derivatives as Novel Allosteric Inhibitors of Branched-chain α-Ketoacid Dehydrogenase Kinase - Tso, Shih-Chia (American Society for Biochemistry and Molecular Biology, 2014)
The mitochondrial branched-chain α-ketoacid dehydrogenase complex (BCKDC) is negatively regulated by reversible phosphorylation. BCKDC kinase (BDK) inhibitors that augment BCKDC flux have been shown to reduce branched-chain amino acid (BCAA) concentrations in vivo. In the present study, we employed high-throughput screens to identify compound 3,6-dichlorobenzo[b]thiophene-2-carboxylic acid (BT2) as a novel BDK inhibitor (IC(50) = 3.19 μm). BT2 binds to the same site in BDK as other known allosteric BDK inhibitors, including (S)-α-cholorophenylproprionate ((S)-CPP). BT2 binding to BDK triggers helix movements in the N-terminal domain, resulting in the dissociation of BDK from the BCKDC accompanied by accelerated degradation of the released kinase in vivo. BT2 shows excellent pharmacokinetics (terminal T(½) = 730 min) and metabolic stability (no degradation in 240 min), which are significantly better than those of (S)-CPP. BT2, its analog 3-chloro-6-fluorobenzo[b]thiophene-2-carboxylic acid (BT2F), and a prodrug of BT2 (i.e. N-(4-acetamido-1,2,5-oxadiazol-3-yl)-3,6-dichlorobenzo[b]thiophene-2-carboxamide (BT3)) significantly increase residual BCKDC activity in cultured cells and primary hepatocytes from patients and a mouse model of maple syrup urine disease. Administration of BT2 at 20 mg/kg/day to wild-type mice for 1 week leads to nearly complete dephosphorylation and maximal activation of BCKDC in heart, muscle, kidneys, and liver with reduction in plasma BCAA concentrations. The availability of benzothiophene carboxylate derivatives as stable BDK inhibitors may prove useful for the treatment of metabolic disease caused by elevated BCAA concentrations.